Attentional foci and coping strategies during matches of young fencers in a training center: a naturalistic video-assisted study - Maurin, M.; Bracco, M.; Le Pape, S.; Lienhart, N.; Bossard, C.; Doron, J.; Martinent, G. (The Sport Psychologist, 2024)
The purpose of this study was twofold: (a) identify attentional foci (AF) and coping strategies used by young fencers during matches and (b) explore the links between these variables using a grounded-theory approach. Using a naturalistic qualitative video-assisted approach, analyses revealed the emergence of five categories of AF (movements and techniques, strategies and tactics, situation evaluation, states, and extraneous attention) and six categories of coping strategies (mastery coping, internal regulation, goal-withdrawal strategies, behavioral regulation, no regulation, and automatic regulation). The grounded theory highlighted that pleasant emotional experiences tended to be related to mastery coping, which in turn favored the orientation of the attention toward AF that appeared to be most effective in winning points (i.e., opponent, distance, plan). Conversely, unpleasant emotional experiences were consistently associated with goal-withdrawal strategies (or no regulation), which generally led to a lack of AF and lower performance. Intervention suggestions are made in relation to the results of the proposed grounded theory.